Effect of Altmetric score on manuscript citations: A randomized-controlled trial. (November 2022) - Peres, Mario FP; Braschinsky, Mark; May, Arne
Background: Alternative metrics to traditional, citation-based metrics are increasingly being used. These are complementary to traditional metrics, like downloads and citations, and give information on how often a given journal article is discussed and used in professional (reference managers) and social networks, such as mainstream media and Twitter. Altmetrics is used in most journals and is available in all indexed headache medicine journals. Whether Altmetrics have an input on traditional, citation-based metrics or whether it is a stand-alone metric system is not clear. Actively promoting a paper through media channels will probably increase the Altmetric score but the question arises whether this will also increase citations and downloads of this individual paper. Methods: Focusing on this point we performed a randomized study in order to test the hypothesis that a promotion intervention would improve citations and other science metric scores. We selected 48 papers published in Cephalalgia from July 2019 to January 2020 and randomized them to either receive an active promotion through social media channels or not. The primary outcome used was the difference between mean article citations with versus without intervention 12 months after the intervention period. Results: The results show that the alternative metrics significantly increased for those papers randomly selected to receive an intervention compared to those who did not. This effect was observed in the first 12 months, right after the boosting strategy was performed. The higher promoted paper diffusion in social media lead to a significantly higher number of citations and downloads. Conclusion: Further promotion strategies should be studied in order to tailor the best cost-benefit intervention.